On the Main Determinants of Start-Up Investment in Developing Countries - Nicola Comincioli; Paolo M. Panteghini; Sergio Vergalli (Center for Economic Studies and ifo Institute (CESifo), 2024)
In this article we study start-up investments in developing countries. Using a representative firm, we wonder how relevant are the effects of taxation and risk on new business activities. It is worth noting that developing countries are usually characterized by three main characteristics. Firstly, a firm's Earnings Before Interest and Taxes (EBIT) is likely to be more volatile than in developed jurisdictions. Secondly, firms in developing countries can be affected by a higher risk of expropriation. In particular, this may happen when early-stage businesses are supported by multinational companies. Thirdly, financial market show higher inefficiencies, compared to countries. Using a real-option approach, we study start-up investment decisions. We find that, although tax rates are usually higher than the developed countries' ones, taxation has an almost negligible effect. If however a policy-maker aims at boosting new business activities it must decrease both EBIT volatility and the expropriation risk, as well as improving financial market efficiency.
Keywords: H25; G33; G38; 330; real options; business taxation; default risk; developing countries; numerical simulations